Theaflavin −3,3'-digallate/ethanol: a novel cross-linker for stabilizing dentin collagen - Chen, Zhiyong; Wei, Yingxian; Liang, Likun; Wang, Xu; Peng, Fangfei; Liang, Yiying; Huang, Xin; Yan, Kaiqi; Gao, Yunxia; Li, Kangjing; Huang, Xiaoman; Jiang, Xinglu; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Objectives: To study the ability of theaflavin-3,3'-digallate (TF3)/ethanol solution to crosslink demineralized dentin collagen, resist collagenase digestion, and explore the potential mechanism.Methods: Fully demineralized dentin blocks were prepared using human third molars that were caries-free. Then, these blocks were randomly allocated into 14 separate groups (n=6), namely control, ethanol, 5 % glutaraldehyde (GA), 12.5, 25, 50, and 100 mg/ml TF3/ethanol solution groups. Each group was further divided into two subgroups based on crosslinking time: 30 and 60 seconds. The efficacy and mechanism of TF3's interaction with dentin type I collagen were predicted through molecular docking. The cross-linking, anti-enzymatic degradation, and biomechanical properties were studied by weight loss, hydroxyproline release, scanning/transmission electron microscopy (SEM/TEM), in situ zymography, surface hardness, thermogravimetric analysis, and swelling ratio. Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy were utilized to explore its mechanisms.Statistical analysis was performed using one and two-way analysis of variance and Tukey's test.Results: TF3/ethanol solution could effectively crosslink demineralized dentin collagen and improve its resistance to collagenase digestion and biomechanical properties (p < 0.05), showing concentration and time dependence. The effect of 25 and 50 mg/ml TF3/ethanol solution was similar to that of 5 % GA, whereas the 100mg/ml TF3/ethanol solution exhibited better performance (p < 0.05). TF3 and dentin type I collagen are mainly cross-linked by hydrogen bonds, and there may be covalent and hydrophobic interactions.TF3 has the capability to efficiently cross-link demineralized dentin collagen, enhancing its resistance to collagenase enzymatic hydrolysis and biomechanical properties within clinically acceptable timeframes (30 s/60 s).Additionally, it exhibits promise in enhancing the longevity of dentin adhesion.